Determinants of Banks’ Profitability in a Developing Economy: Evidence From Nigeria - Obamuyi, Tomola Marshal (Organizations and Markets in Emerging Economies, 2013)
The unimpressive banks’ performance in Nigeria over the last decade has remained a source of concern for all and sundry. This study investigates the effects of bank capital, bank size, expense management, interest income and the economic condition on banks’ profitability in Nigeria. The fixed effects regression model was employed on a panel data obtained from the financial statements of 20 banks from 2006 to 2012. The results indicate that improved bank capital and interest income, as well as efficient expenses management and favourable economic condition, contribute to higher banks’ performance and growth in Nigeria. Thus, government policies in the banking system must encourage banks to regularly raise their capital and provide the enabling environment that will accelerate economic growth in the country. Bank management must efficiently manage their portfolios in order to protect the long run interest of profit-making.